Pengaruh Penggunaan Gadget terhadap Ketertarikan dan Keterlibatan Belajar Siswa IPS di SMP Negeri 2 Kauman Tulungagung (Lembaga Pengembangan Kinerja Dosen, 2026)
Although gadgets provide students with rapid access to a wide range of learning resources, their presence in instructional settings may also generate off-task attention when academic use is not properly regulated. This research assessed the statistical influence of gadget use on the learning interest and learning engagement of eighth-grade students in Social Studies at SMP Negeri 2 Kauman Tulungagung. The study employed a quantitative ex post facto design. A purposively selected sample of 119 students from classes VIII A, VIII C, VIII D, and VIII E was drawn from a population of 301 students. Data were gathered through three Likert-scale questionnaires, each consisting of eight items, covering gadget use, learning interest, and learning engagement. Every item satisfied the validity requirement, and Cronbach’s alpha values ranged between 0.733 and 0.815. Simple linear regression demonstrated a positive and statistically significant influence of gadget use on learning interest (B = 0.629; t = 10.655; p < 0.001; R² = 0.492) and learning engagement (B = 0.682; t = 12.022; p < 0.001; R² = 0.553). These findings indicate that gadgets can support students’ attention, enthusiasm, and active participation when their use is academically purposeful and adequately supervised. Accordingly, access to digital resources should be accompanied by explicit usage boundaries and sustained guidance from schools and families.